Die Konstruktion von Reputation -- Verweise auf Ferdinand de Saussure in der romanistischen Sprachwissenschaft - Richter, Julia (DiskursNetz, 2015)
How do linguists become famous? Or are they made famous by others? This volume sheds light on strategies of the construction of reputation by way of the discourses on Ferdinand de Saussure in linguistics and romance studies.